The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.4102/sajcd.v69i2.905
|View full text |Cite
|
Sign up to set email alerts
|

Simulations as a mode of clinical training in healthcare professions: A scoping review to guide planning in speech-language pathology and audiology during the COVID-19 pandemic and beyond

Abstract: Simulations as a mode of clinical training in healthcare professions: A scoping review to guide planning in speech-language pathology and audiology during the COVID-19 pandemic and beyond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Furthermore, as far as challenges to practice are concerned, COVID-19 significantly increased the workload of clinicians (Balton et al, 2022 ; Hlayisi, 2022 ; Khatib & Hlayisi, 2022 ). Over and above the core function of providing clinical care, time devoted to establishing innovative modes of service provision, sourcing required resources that would allow for continuity of service provision during the pandemic, training and upskilling everyone on alternative service provision methods, as well as engagement in the national COVID-19 pandemic management were all added to clinicians’ workloads (Achmat & Gerber, 2022 ; Balton et al, 2022 ; Hlayisi, 2022 ; Karrim et al, 2022 ; Khatib & Hlayisi, 2022 ; Khoza-Shangase, 2022b ; Nagdee et al, 2022 ). Balton et al ( 2022 ) highlighted how such workload challenges were possibly influenced by a lack of or poor application of policies and regulations within the South African context.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as far as challenges to practice are concerned, COVID-19 significantly increased the workload of clinicians (Balton et al, 2022 ; Hlayisi, 2022 ; Khatib & Hlayisi, 2022 ). Over and above the core function of providing clinical care, time devoted to establishing innovative modes of service provision, sourcing required resources that would allow for continuity of service provision during the pandemic, training and upskilling everyone on alternative service provision methods, as well as engagement in the national COVID-19 pandemic management were all added to clinicians’ workloads (Achmat & Gerber, 2022 ; Balton et al, 2022 ; Hlayisi, 2022 ; Karrim et al, 2022 ; Khatib & Hlayisi, 2022 ; Khoza-Shangase, 2022b ; Nagdee et al, 2022 ). Balton et al ( 2022 ) highlighted how such workload challenges were possibly influenced by a lack of or poor application of policies and regulations within the South African context.…”
Section: Resultsmentioning
confidence: 99%
“…With the overall recommendation of hybrid models of teaching and learning that include the use of ICT, simulations, teletraining and telesupervision (Barber & Sher, 2022 ; Masuku & Mupawose, 2022 ; McAllister et al, 2022 ; Nagdee et al, 2022 ), Naidoo et al ( 2022 ) stressed that online platforms will facilitate closer and increased collaboration. This collaboration is between students and between students and educators, with increased opportunities for local and international collaborations.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy-two per cent of the audiology students who participated in the study conducted by Thome et al ( 2020 ) in their survey reported that in-person clinical training was more effective than receiving clinical training through simulations and telepractice. However, traditional in-person clinical training and simulations were complementary learning approaches that improved clinical competency and students’ clinical training experience (Nagdee et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…11 Researchers from other allied health professions, such as occupational therapy and speech-language pathology, also published responses to the COVID-19 pandemic indicating similar disruptions to the educational environment. [12][13][14][15] However, there are no published reports of the effects of the COVID-19 pandemic specifically on physical therapy CEEs.…”
Section: Review Of Literaturementioning
confidence: 99%